EFL Teacher’s Beliefs on the Use of Word Mapping Strategy in Vocabulary Learning - Rosalina, Mega Putri; Zur, Sarjaniah; Abidin, Azwar (AL LUGHAWIYAAT, 2023)
This study aims to explore the beliefs of the lecturer when applying the use of word mapping strategy in vocabulary learning. This study used qualitative research with explanatory case studies. The data of this study was obtained from reflection and interviews with one participant. The participant is an English lecturer at one of the universities in Kendari in the academic year 2021/2022. In analyzing the data, the researcher collects the data, prepares data for analysis, codes the data, and describes it to be used in the research paper. Further, the following reveals how the data analysis process is obtained through reflections and lecture interview answers. To analyze the data, the researcher used thematic analysis. Moreover, the result of the reflection and interview sessions found three themes about teachers' beliefs. They are word mapping as an appropriate strategy in vocabulary learning; word mapping strategy builds students' awareness in learning vocabulary; word mapping as a strategy in classroom management. This study implies that the use of teacher’s beliefs by using a word mapping strategy could give understanding to the teacher how to do quality teaching and make students feel enthusiastic by the interesting media in learning vocabulary. Keywords: Teacher’s beliefs, Vocabulary learning, Word mapping strategy,